Analisa Data Radiosonde Dengan Menggunakan Bahasa Pemrograman Phyton - Apriadi; Heri Suroyo (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The results of this research are flying a radiosonde sensor using a 200g Totex balloon to determine the extreme point of the Planetary Boundary Layer using the potential temperature gradient method from radiosonde sensor data and knowing the procedure for using a radiosonde tool to obtain radiosonde sensor height estimation data and atmospheric layer data This produces extreme points from different atmospheric boundary layers, the extreme point is located at an altitude of 19,000 to 27,000 with the lowest potential temperature value at 0.047593746 to the highest at 0.349642987. then the results of the extreme points from the Planetary Boundary Layer will be graphed using Phyton coding to get accurate extreme points. And the benefit of this research is to obtain information about the Planetary Boundary Layer in fire-prone areas and can also be used by climatologists and Planetary Boundary Layer (PBL) researchers using radiosondes in Indonesia.